Molecular epidemiology of Theileria parva in the field - Geysen, D.; Bishop, Richard P.; Skilton, Robert A.; Dolan, T.T.; Morzaria, S.P. (Wiley, 1999)
Molecular tools based on seminested RFLP-PCR techniques to characterize field parasites in bloodspots dried on filter paper permitted investigation of the extent and the dynamics of diversity of Theileria parva populaitons in the field. Parallel molecular studies explored the long-term genome stability of various isolates by probing Southern blots of EcoRI digested total genomic DNA with four different reference nuclei acid probes. Three polymorphic single copy loci encoding for antigen genes were developed for seminested PCR detection in order to apply them for a multilocus approach in population genetic studies. Seven alleles were identified for the polymorphic immunodominant molecule (PLM) locus by using restriction enzymes, and 4 alleles each for the p150 and p104 loci. A simple DNA extraction method gave good results in amplifying these loci from carrier animals using samples of blood dried on filter papers. Results from probing Southern blots of cultures taken at sequential timepoints indicate relative genome stability in T. parva in comparison to other parasitic protozoa such as Plasmodium. Comapratively homogeneous profiles in sympatric isolates from Zambia were identified using all four probes and PCR amplified products which contrasted with the variety found amongst Kenyan stocks. Preliminary characterization of T. parva field samples from the Southern Province of Zambia strongly suggest clonal expansion of one of the components of a non-Zambian trivalent vaccine used on a limited scale in the Province from 1985 until 1992.